ANALISIS JUMLAH UANG BEREDAR M2 DAN TINGKAT SUKU BUNGA TERHADAP PERTUMBUHAN EKONOMI DI KALIMANTAN BARAT - B01108025, Syafari (Jurnal Pembangunan dan Pemerataan, 2013)
The title of the study is "Money Supply Analysis and Growth Rate Against West Kalimantan". This study aimed to determine the effect of the money supply and interest to economic growth western Kalimantan and analyze the elasticity of the money supply and interest rates to economic growth western Borneo. This study uses time series data since 2001 first quarter to 2010 fourth quarter, which is the data from the Central Bureau of Statistics and Bank Indonesia. This study using correlative and regression analysis using eviews program. Based on the estimates, the study found that the variables that affect the amount of money supply and interest rates have a very strong relationship to economic growth. Money supply variables significantly influence economic growth and interest rates that significantly influence economic growth. Test results obtained from the elasticity of the elasticity of the money supply and interest rates to economic growth is elastic West Kalimantan. Based on the classic assumption test found that the estimates of the regression model containing positive autocorrelation, does not contain muktikolinearitas, and contains no heterocedastisity. Keywords: Keywords: Economic Growth, Money Supply and Interest Rates.